Studying the effects of booster shots and antibody responses to the SARS-CoV-2 vaccination over time in health personnel - Wu, Jingjing; Mu, Hanyou; Pan, Xiaowan; Guo, Wenzheng (Frontiers in Cellular and Infection Microbiology, 2023)
Background: With the emergence of mutant versions that lead to continual spreading and recurrent infections of SARS-CoV-2, the COVID-19 vaccines can assist protection for high risk groups, particularly health workers. Even while booster shots have been widely used, longitude studies on immune responses in healthy subjects are uncommon. Methods: Eighty-five healthcare workers who received the BBIBP-CorV vaccine were prospectively enrolled and monitored for up to ten months. Automated Pylon immunoassays were used to quantify total anti-SARS-CoV2 antibody levels (TAb), surrogate neutralization antibody levels (NAb), and antibody avidities over the course of the follow-up. Additionally, hematology analyses were performed. Results: Pylon antibody testing revealed that every participant tested negative at the beginning, and 88.2% of them tested positive about 14 days after receiving their second dosage. The TAb levels and NAb levels peaked in 76.5% and 88.2% of the subjects, respectively, at the same time. Age was connected with the peak antibody levels, but not with gender, BMI, or baseline hematological factors. The positive rates and the antibody levels had already started to decline three months following the second injection. The antibody levels and avidities quickly increased following the booster doses to levels that were considerably greater than the peak antibody responses before to the booster shots. Hematology testing revealed no safety concerns with immunizations. Conclusions: In healthy workers, the two doses of BBBP-CorV were able to induce humoral immunity; however, 3 months following vaccination, the antibody levels started to decline. The BBBP-CorV booster injections increase both the quantity and quality of antibodies, which gave support for utilizing booster doses to prolong the duration of the vaccine's protective effects.